Trixie - Alan, Rudolph; Murphy, Brittany, 1977-; Dermot Mulroney; Lesley Ann Warren; Nathan Lane; Nick Nolte; Will Patton; Emily Watson (USA : Pandora Cinema., 2000)
Emily Watson stars as Trixie, an eccentric woman who aspires to quit her job as a security guard and become a private detective. However, comedy intervenes and the mess begins...
An eccentric, unconventional woman whose naive aspirations to rise from her job as a security guard to full-fledged private eye lead her into a tangled PL: mess.
Alan Rudolph
Languages: Turkish, English Subtitles: Turkish, English
Keywords: Crime; Mystery; Comedy